2022
DOI: 10.1177/07417136221080424
|View full text |Cite
|
Sign up to set email alerts
|

Post-Truth as an Epistemic Crisis: The Need for Rationality, Autonomy, and Pluralism

Abstract: Contemporary society is experiencing an epistemic crisis, evidenced by such “post-truth” phenomena as “alternative facts.” Traditional notions related to knowledge and Truth have been under continual, partly justifiable, attack under the eclectic banner of postmodernism, and alternative epistemic foundations (essential for democracy to function) have not been provided. Drawing on the European and North American literature of political theory, philosophy, and adult education, this article offers an update and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although this study did not investigate age's relationship with the teaching and learning of reflection, research has identified age-related changes in decision-making that may be relevant to future research (see Mikels et al, 2015; Peters, 2010; Tymula et al, 2013; Zakirov & Krasilnikov, 2020). Perhaps most importantly, recent findings have shown that older adults may exhibit different dispositions toward types 1 and 2 reasoning than younger adults (Hertzog et al, 2018). Such findings would suggest differential effects for instructional strategies that aim to develop reflective habits in adult learners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study did not investigate age's relationship with the teaching and learning of reflection, research has identified age-related changes in decision-making that may be relevant to future research (see Mikels et al, 2015; Peters, 2010; Tymula et al, 2013; Zakirov & Krasilnikov, 2020). Perhaps most importantly, recent findings have shown that older adults may exhibit different dispositions toward types 1 and 2 reasoning than younger adults (Hertzog et al, 2018). Such findings would suggest differential effects for instructional strategies that aim to develop reflective habits in adult learners.…”
Section: Discussionmentioning
confidence: 99%
“…Today, perhaps more so than at any other time in history, educators must help adults develop the habit of stopping to reflect. The age of information and uncertainty has inundated adults with conflicting information (Harford, 2021), introducing them to such novel phenomena as "alternative facts" (Hoggan-Kloubert & Hoggan, 2022) and "fake news" (Michelson, 2019). Springing from this epistemic chaos is a global, interconnected world that frequently presents adults with complex problems involving multiple stakeholders, unclear actions, and unintended consequences (Grint, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…By its very nature, democracy “is the most cognitively demanding form of living together, presupposing many human capacities (e.g., critical decision-making) and social processes (e.g., public deliberation)” (Hoggan-Kloubert & Hoggan, 2023, p. 6), which is why adult education has long been positioned as its necessary companion. Adult education, however, can be used to serve many purposes.…”
Section: The Foundation For An Ethics Of Adult Educationmentioning
confidence: 99%
“…Adult and lifelong education, given its historical emphasis on the connections between democracy, education, and informed civic engagement, is an important site of intellectual and practical work in restoring democratic practices. Recent research theorizes about the rise of populism and totalitarianism, the influence of "post truth" society, the impacts of technology and social media on communities, the role of adult learning in civic society, and how adult learning connects simultaneously as an explanation of as well as a remedy to addressing increasing radicalization sweeping our political landscape (Fleener & Barcinas, 2022;Hoggan-Kloubert & Hoggan, 2022;Horton & Friere, 1990;Petrie et al, 2019;Schroeder et al, 2019). Democracies worldwide are struggling to make sense of and respond to the changing landscapes and citizen engagement in the democratic process.…”
Section: Historical Perspectives Of Adult and Lifelong Learningmentioning
confidence: 99%